دور لجان التدقيق في تفعيل نظام الرقابة الداخلية بمؤسسة مطاحن عمر بن عمر – قالمة - - مريم شابي; أحلام مرابط (My University, 2021)
This study addresses the role of the audit committees in the activation of the internal control system , where the Amor Benamor Mills foundation was field study. The aim of field dtudy was to highlight the role played by the duf committees in improving and activating the internal control system in touch by uncovering the mechanisms of the work of the audit committees , in ordre to ascertain This , it shed light on the concpet of Such committees , it identified the Most important characteristics That should exist in them That would give effect to roles they play , And it also identified the importance and objectives of the internal control system and the supporting elements , including the audit committees that are engaged in evaluding internal control systems contribute to thir efficiency. The study concluded that the role of audit committees contributes significantly to activating and improving the internal control system in the institution ....................................................... تهدف هذه الدراسة دور لجان التدقيق في تفعيل نظام الرقابة الداخلية ، حيث تم استخدام مؤسسة مطاحن عمر بن عمر -قالمة-كنموذج للدراسة الميدانية. وقد هدفت هذه الدراسة إلى إبراز الدور الذي تقوم به لجان التدقيق في مجال تحسين وتفعيل نظام الرقابة الداخلية بالمؤسسة وذلك من خلال الكشف عن آليات عمل لجان التدقيق ، وللتحقق من ذلك فقد تم تسليط الضوء على مفهوم هذه اللجان والتعرف على أهم العوامل التي أدت إلى انتشاره في السنوات الأخيرة بالدول المتقدمة ، وأيضا معرفة أهم الخصائص التي ينبغي توافرها فيها والتي من شانها تفعيل الأدوار التي تقوم بها ، وكذا إلى أهمية وأهداف نظام الرقابة الداخلية والعناصر الداعمة لو بما في ذلك لجان التدقيق التي تعمل على تقييم أنظمة الرقابة الداخلية مما يساهم في زيادة فاعليتها . وقد توصلت الدراسة بان الدور الذي تقوم به لجان التدقيق يساىم بشكل كبير في تفعيل وتحسين نظام الرقابة الداخلية بالمؤسسة